Perception of Redirected Pointing Precision in Immersive Virtual Reality - Debarba, Henrique G; Khoury, Jad-Nicolas; Perrin, Sami; Herbelin, Bruno; Boulic, Ronan (2018 IEEE Conference on Virtual Reality and 3D User Interfaces (VR), 2018)
We investigate the self-attribution of distorted pointing movements in immersive virtual reality. Participants had to complete a multidirectional pointing task in which the visual feedback of the tapping finger could be deviated in order to increase or decrease the motor size of a target relative to its visual appearance. This manipulation effectively makes the task easier or harder than the visual feedback suggests. Participants were asked whether the seen movement was equivalent to the movement they performed, and whether they have been successful in the task. We show that participants are often unaware of the movement manipulation, even when it requires higher pointing precision than suggested by the visual feedback. Moreover, subjects tend to self-attribute movements that have been modified to make the task easier more often than movements that have not been distorted. We discuss the implications and applications of our results.